Social and Cultural Transformations of the Russian Society and Modern Innovative Strategies from the Perspective of Synergetic Analysis - Shcherbakova, Anna Iosifovna; Selezneva, Elena Nikolaevna; Kamenets, Alexander Vlaldlenovich; Korsakova, Irina Anatolievna; Gorbacheva, Elena Gennadievna (International Review of Management and Marketing, 2016)
The article dwells upon basic problems of social and cultural transformations of the Russian society and highlights the potential of synergetic dynamics of this process. A special stress is laid upon spiritual and moral objectives and goal-settings. The authors analyse macro- and microlevels of synergetic factors and their integrity as part of the modernisation of the Russian society. This article also touches upon structural and functional approaches towards the analysis of synergetic processes; it studies various scenarios and strategies of the above-mentioned social and cultural transformations of the Russian society. Moreover, the authors consider traditional and innovative synergetic factors in modernisation processes. Unparalleled attention is paid to the possible formation of new norms and regulations of social behaviour as synergetic dynamics determining the development of social systems. The authors analyse the role of religion in synergetic processes within the Russian spiritual traditions, define the connection between economic development and changes in basic social values. Within the article the study of the Russian society as a developing system has been conducted with the help of structural and functional analysis. Thereby, the authors present both theory and practice of the modernization process of modern societies as exemplified by the Russian society and perspectives of its further synergetic study. Keywords: synergetics, transformations, commune, society, innovations, traditions, evolution, JEL Classifications: Z00, Z10, Z11.